2010
DOI: 10.1016/j.jacc.2010.04.068
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Receptor Signaling Mitigates Renal Dysfunction-Associated Heart Failure by Mechanisms Unrelated to Relief of Anemia

Abstract: EPO receptor signaling exerts direct cardioprotection in an animal model of renal dysfunction-associated heart failure, probably by mitigating degenerative, pro-fibrosis, inflammatory, and oxidative processes but not through relief of anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…We previously reported that asialoEPO restored GATA-4 expression in CKD-associated heart failure. 14 We suggest that the beneficial effects of asialoEPO on GATA-4 expression, myofibrillar content, and sarcomeric integrity are key elements underlying the observed improvement in cardiac function in the failing hearts, as these changes would directly influence the contractile power of individual cardiomyocytes. AsialoEPO indicates asialoerythropoietin; 2, the strength of the phenotype is less than in the sham or wild type; 1, the strength of the phenotype is greater than in the sham or wild type; 3, the strength of the phenotype is similar to the sham or wild type.…”
Section: Mechanisms Underlying the Beneficial Effects Of Asialoepomentioning
confidence: 89%
See 3 more Smart Citations
“…We previously reported that asialoEPO restored GATA-4 expression in CKD-associated heart failure. 14 We suggest that the beneficial effects of asialoEPO on GATA-4 expression, myofibrillar content, and sarcomeric integrity are key elements underlying the observed improvement in cardiac function in the failing hearts, as these changes would directly influence the contractile power of individual cardiomyocytes. AsialoEPO indicates asialoerythropoietin; 2, the strength of the phenotype is less than in the sham or wild type; 1, the strength of the phenotype is greater than in the sham or wild type; 3, the strength of the phenotype is similar to the sham or wild type.…”
Section: Mechanisms Underlying the Beneficial Effects Of Asialoepomentioning
confidence: 89%
“…*Data on nephrectomy-induced heart failure from Ogino et al 14 Induction of powerful inflammatory mediators is reportedly associated with heart failure. 19,20 Inflammatory reactions often are associated with oxidative stress in a vicious cycle in which inflammatory mediators and various oxidants induce and exacerbate one another.…”
Section: Mechanisms Underlying the Beneficial Effects Of Asialoepomentioning
confidence: 99%
See 2 more Smart Citations
“…37 AEPO is one of the candidates to avoid platelet activation because the serum level of AEPO does not elevate while preserving their angiogenic (PCT Patent 2006/129755) and cardioprotective effects but not erythropoietic effects. 38 HEPO is another candidate. HEPO reveals tissue affinity, and thus probably does not to show a rapid rise in blood.…”
Section: Discussionmentioning
confidence: 99%